Do men and women accumulate assets in different ways? Evidence from rural Bangladesh - Quisumbing, Agnes R. (International Food Policy Research Institute, 2011)
This paper examines asset dynamics for husband-owned, wife-owned, and jointly owned assets, using unique longitudinal survey data from rural Bangladesh. Nonparametric and parametric methods are used to examine the shape of the dynamic asset frontier, the number of equilibria, and whether land and nonland asset stocks converge to such equilibria. The paper also investigates the differential impact of negative shocks and positive events on husbands', wives', and jointly owned assets. Husbands' and wives' asset stocks are drawn down for different kinds of shocks, with husbands' assets being liquidated in response to death of a household member and dowry and wedding expenses, and both husbands' and wives' assets being negatively affected by illness shocks. The paper concludes by drawing out implications for the design of gender-sensitive social protection mechanisms.